Home price dynamics: A behavioural economy? - Smith, Susan (Routledge, 2011)
Housing is a hot topic for economists, sparking numerous lively debates. Many of these address the vexed question of price: its micro-economic foundations and its macro-economic effects. Notwithstanding significant achievements, however, economics has struggled to account for home price dynamics using tried and tested tools. At the same time, other disciplines, ostensibly well placed to contribute, have tended to stand back. As the analytical task becomes more urgent, this paper considers the scope for rapprochement. Can cross-disciplinary alliances help establish whether housing markets are driven by hidden hands, animal spirits or some other financial intelligence?. © 2011 Copyright Taylor and Francis Group, LLC.